Exploration of PDCoV-induced apoptosis through mitochondrial dynamics imbalance and the antagonistic effect of SeNPs - Ren, Zhihua; Yu, Yueru; Zhang, Xiaojie; Wang, Qiuxiang; Deng, Junliang; Chen, Chaoxi; Shi, Riyi; Wei, Zhanyong; Hu, Hui (Frontiers in Immunology, 2022)
Porcine Deltacoronavirus (PDCoV), an enveloped positive-strand RNA virus that causes respiratory and gastrointestinal diseases, is widely spread worldwide, but there is no effective drug or vaccine against it. This study investigated the optimal Selenium Nano-Particles (SeNPs) addition concentration (2 - 10 μg/mL) and the mechanism of PDCoV effect on ST (Swine Testis) cell apoptosis, the antagonistic effect of SeNPs on PDCoV. The results indicated that 4 μg/mL SeNPs significantly decreased PDCoV replication on ST cells. SeNPs relieved PDCoV-induced mitochondrial division and antagonized PDCoV-induced apoptosis via decreasing Cyt C release and Caspase 9 and Caspase 3 activation. The above results provided an idea and experimental basis associated with anti-PDCoV drug development and clinical use.